Dietary fiber intake and non-alcoholic fatty liver disease: The mediating role of obesity - Yu Zhu; Yu Zhu; Hu Yang; Yaozong Zhang; Songxian Rao; Yufeng Mo; Honghua Zhang; Shaoxian Liang; Zhuang Zhang; Wanshui Yang (Frontiers Media S.A., 2023)
Background and aimsDietary pattern rich in fiber is negatively associated with the risk of non-alcoholic fatty liver disease (NAFLD). Meanwhile, obesity is a known predisposing factor for NAFLD. Nutrient-focused research can enhance the mechanistic understanding of dietary effects. We thus hypothesized that higher dietary fiber intake was associated with lower risk of NAFLD through the mediating role of obesity.MethodsIn this nationwide cross-sectional study, dietary fiber was surveyed using two 24-h recalls. NAFLD and clinically significant fibrosis (CSF) were determined by vibration-controlled transient elastography. Multivariable logistic and linear regression were applied to investigate the association of dietary fiber with NAFLD, CSF, and liver function parameters. We used counterfactual-based mediation analysis to estimate the direct and indirect effect of dietary fiber on NAFLD.ResultsOf the 3,974 participants, ~36.86% and 7.78% of participants were diagnosed with NAFLD and CSF. Compared with participants among the lowest tertile, the highest tertile of dietary fiber consumption was associated with lower odds of NAFLD (OR = 0.81; 95% CI: 0.66-0.98; Poverall = 0.019). Dietary fiber intake appeared to be linked with lower odds of CSF (ORTertile3vs.Tertile1 = 0.81; 95% CI: 0.58-1.14; Poverall = 0.107). Mediation analysis showed that obesity fully mediated the association of dietary fiber with NAFLD. Dietary fiber was associated with improved hepatic parameters.ConclusionsThe findings indicated that increasing dietary fiber intake could confer a greater benefit to protect against NAFLD. Translating these findings regarding dietary fiber into dietary advice might be an attractive strategy for NAFLD prevention.